1995
DOI: 10.3382/ps.0740771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Particle Size on Performance.

Abstract: Three experiments were conducted to study the effect of particle size obtained by grinding wheat and sorghum in a hammer mill (HM) or roller mill (RM) on broiler performance. Broilers were fed a mash diet or crumbles to 4 wk of age, then pellets to 7 wk of age. When fed as a mash, diets produced with RM-ground grain improved performance. The effect of grinding was additive to that of pelleting. The interactive effects observed between grinding method and the form of the feed on body weight and feed intake were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
4
12

Year Published

1997
1997
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(84 citation statements)
references
References 17 publications
12
56
4
12
Order By: Relevance
“…This coincided with the greater digestibility of EE (9.5%) and CF (23.4%), and resulted in a higher production index (27.5%). These results are similar to those reported by Nir et al (1995), Engberg et al (2002), Svihus et al (2004) and Cutlip et al (2008). These improvements have been variously attributed to increased nutritional density, increased nutrient intake, changes in the physical form of the feed, reduced feed wastage, decreased energy expenditure while eating (McKinney and Teeter, 2004;Skinner-Noble et al, 2005;Amerah et al, 2007;Cerrate et al, 2009;Yang et al, 2010), increased starch digestibility (Parsons et al, 2006), and improved apparent metabolisable energy (AME) and nutrient retention (Svihus et al, 2004;Adeyemi et al, 2008) mechanical action resulted in a rupture of the cell walls and thus made encapsulated nutrients of the feedstuff more accessible to digestive enzymes (Vande and Schrijver, 1988;Cutlip et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…This coincided with the greater digestibility of EE (9.5%) and CF (23.4%), and resulted in a higher production index (27.5%). These results are similar to those reported by Nir et al (1995), Engberg et al (2002), Svihus et al (2004) and Cutlip et al (2008). These improvements have been variously attributed to increased nutritional density, increased nutrient intake, changes in the physical form of the feed, reduced feed wastage, decreased energy expenditure while eating (McKinney and Teeter, 2004;Skinner-Noble et al, 2005;Amerah et al, 2007;Cerrate et al, 2009;Yang et al, 2010), increased starch digestibility (Parsons et al, 2006), and improved apparent metabolisable energy (AME) and nutrient retention (Svihus et al, 2004;Adeyemi et al, 2008) mechanical action resulted in a rupture of the cell walls and thus made encapsulated nutrients of the feedstuff more accessible to digestive enzymes (Vande and Schrijver, 1988;Cutlip et al, 2008).…”
Section: Discussionsupporting
confidence: 93%
“…Those authors did not observe any influence of feed physical form on cecum weight. Although Dahlke et al (2003) and Nir et al (1995) demonstrated that dietary particle size affects intestinal weight and size, Garcia et al (2005), did not observe any effect of the substitution of corn by sorghum on intestinal relative weight, which is consistent with the findings of the present study.…”
Section: Resultssupporting
confidence: 83%
“…Essa maior precocidade da linhagem Cobb, somada ao grande consumo das rações peletizadas, pode aumentar a necessidade de oxigênio com conseqüente aumento da incidência de doenças metabólicas. Estes resultados foram semelhantes aos observados por Nir et al (1995) e Leeson et al (1999) Bertechini et al (1991b), Murakami et al (1995) e Stringhini et al (2003. Meinerz et al (2001) Com relação à linhagem é importante ressaltar semelhanças em relação às principais variáveis de desempenho (consumo e conversão alimentar) e rendimento de cortes nobres (peito e coxas + sobrecoxas), com exceção do ganho de peso, em que as aves da linhagem Cobb, alimentadas com ração peletizada, obtiveram maiores ganhos; e da viabilidade, em que as aves da linhagem Cobb, também alimentadas com rações peletizadas, apresentaram maior susceptibilidade às doenças metabólicas (ascite e morte súbita).…”
Section: Resultsunclassified